Dislocation plasticity and detwinning under thermal stresses in nanotwinned Ag thin films. (1st October 2020) - Kini, Maya K.; Merola, Claudia; Breitbach, Benjamin; Klapproth, Dennis; Philippi, Bastian; Molin, Jean-Baptiste; Kirchlechner, Christoph; Dehm, Gerhard
Abstract: Wafer curvature measurements reported in literature for polycrystalline (often textured) and epitaxial fcc metal thin films on hard substrates show a characteristic "signature" in the stress-temperature evolution for either type of films. While epitaxial films reveal characteristic elastic – ideal plastic deformation with no dislocation storage and highly repeatable cycles, polycrystalline films show considerable hardening upon cooling in addition to the relaxation by diffusional creep at elevated temperatures. In the present study, we study the deformation characteristics of an electron beam deposited epitaxial nanotwinned Ag on Si (111) substrate. The twin spacing λ of the nanotwinned Ag is controlled by suitable heat treatment and the "signature" thermomechanical deformation curves by wafer curvature measurements are recorded for twin spacings varying from 20 nm to 1 μm. Further, deformation is compared to other small scale deformation studies on fcc metals such as epitaxial bicrystal films, bicrystal micropillars containing a coherent twin boundary and nanotwinned micropillars. Graphical abstract: Image, graphical abstract